Effectiveness of an integrated-Weight Management Programme (i-WMP) in reducing body weight among noncommunicable disease patients in Malaysian government primary care clinics: a randomised controlled trial - Tan, Siew Tin; Mohd Sidik, Sherina; Rampal, Lekhraj; Tan, Kit Aun; Ibrahim, Zuriati; Ahmad, Norliza; Mustapha, Ummu Kalsum; Paimin, Fuziah; Talib, Nor Hazlin; Sharifuddin, Naemah; Ibrahim, Normala (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: Obesity is a global issue called as “globesity”. Overweight and obesity may lead to many noncom- municable diseases (NCDs). Primary care is the first centre to monitor and follow-up the progress of NCD patients. Therefore, the objective of this study was to determine the effectiveness of an integrated-Weight Management Pro- gramme (i-WMP) to reduce body weight among NCD patients from two Government primary care clinics from Hulu Langat District. Methods: This study was single-blinded randomised controlled trial by design. There were 244 eligible patients were randomised into intervention (n = 122) or wait-list control group (n = 122). The i-WMP was developed based on the behaviour change wheel through the operationalization of behaviour change techniques. The duration of this intervention programme was four weeks. Data collected at week 0, week 4, and week 12. The software IBM SPSS was used to analyse the data. Generalized linear mixed model analysis with intention-to-treat principle was applied. Results: The retention rate was 74.2%. Findings showed that the i-WMP was significantly effective in reducing not only body weight as primary outcome but also secondary outcomes such as waist-to-height ratio, waist circumference, body mass index, and total sitting time. It also improved effectively other secondary out- comes such as participants’ knowledge, attitude, and practice towards dietary and towards physical activity. Howev- er, no significant changes were reported for body fat percentage and total physical activity metabolic equivalent of task-minutes/week. Conclusion: Implications surrounding the implementation of i-WMP in the primary care clinics are recommended.